Rasio Keuangan Prediktor Kondisi Financial Distress di Masa Pandemi COVID-19 pada Perusahaan Properti dan Real Estate - Arnita, Azka Halimah Nur; Ida, Ida (Research Center and Case Clearing House PPM School of Management, 2024)
The condition of the Indonesian economy, which is currently unstable due to the COVID-19 pandemic situation, has had an impact on sub-sector companies, especially property and real estate sub-sector companies. The impact felt by companies in the property and real estate sub-sector is when people experience a change in attitude to restrain consumption of long-term asset needs. This research aims to know the effect of CR, TATO, DER, ROA, and operating cash flow on financial distress. The sample collection method uses the purposive sampling method, namely property and real estate sub-sector companies listed on the IDX 2020-2021 and the category of financial distress with negative net profit for two consecutive years. Statistical analysis technique using logistic regression with the help of SPSS 25 with α 5%. The study's results prove that the ratios of CR, DER, and Operating Cash Flow do not affect financial distress. At the same time, TATO has a positive effect, and ROA has a negative effect on a company's financial distress. Companies can maximize their assets to increase sales and net profit so that it can be said to be effective, but companies need to manage the costs incurred for the process of their operational activities. Companies can use TATO and ROA to anticipate financial distress or difficulties.